STUDENTS’ PERCEPTIONS OF THE TEACHERS’ TEACHING CONCEPTIONS: A CASE OF ENGLISH TEACHER TRAINING AND EDUCATION PROGRAM - Astrid Marcella; - Luciana (Universitas Katolik Indonesia Atma Jaya, 2011)
This study reported students’ perceptions of the teacher’s teaching conceptions in an English Teacher Training and Education Program in Indonesia. The teaching conceptions were based on Freeman and Richardson’s (1993) three types of teaching conceptions: scientifically based, theory-and-values based, and art or craft based conceptions. The study involved 218 participants from three different batches (2008, 2009, and 2010). Obtaining the data from the questionnaires and interviews, this study found that the three batches shared the same perceptions of several items in each teaching conception. In the science/research conception, they agreed on the teachers’ applying learning principles and using an effective classroom practice model. As for the theory/philosophy conception, they similarly perceived the teachers’ incorporating values into teaching, conveying communicative approach, referring to theories, giving moral values through teaching, presenting themselves as a role model in morality, and presenting their teaching rationally. Their perceptions were also confirmed by the interview revealing that the students tended to see their teachers’ teaching conceptions as theory/philosophy based. Regarding the art/craft conception, they similarly noted the teachers’ helping them to understand how to develop their ability and skills as future teachers. The analysis using a one-way analysis of variance (ANOVA) further confirmed that the three batches were not significantly different with P = .658. They expected the teachers to hold art/craft based teaching conception because they believed that understanding them as learners was the key for successful learning.Keywords: students’ perceptions, teachers’ teaching conceptions, scientifically based, theory-and-values based, and art or craft based conceptions.